(untitled) (Journal of Sustainability, Environment and Peace, 2020)
The importance of historical rainfall pattern in gaining a sound understanding of climate change in any particular region is paramount. This study investigated rainfall variability at Wiyumiririe location of Ngobit ward, Laikipia County Kenya. The study sought to gain insight into rainfall variability, intensity, and frequency of droughts and wet periods as a pointer to the distribution, reliability and total amount of rainfall received both for the long and short growing seasons. The study relied on historical rainfall data derived from the nearby Lamuria weather station (code: 9036213; 0o08’S 36o 52’E) operated by the Water Management Authority (WMA) for Kenya Meteorological Department (KMD), for the period between January 1958 and December 2017. The choice of the weather station was based on the fact that it was the only one of its kind within a radius of 100 kms from the study site and in the same Agro Climatic Zone V. Moreover, it contained credible historical weather data. Rainfall Anomaly Index (RAI) was used for analysis. Results of the study showed that over the years, the total amount of rainfall was declining; the frequency and intensity of droughts are increasing while the wet periods are reducing in numbers and intensity. Therefore, for farmers to improve food security and adapt to the changing climate, there is a need to focus on how to maximize on the available rainwater while at the same time remain cognizant of the changing patterns of rainfall. The significance of the study was that the information is likely to help farmers and policy makers make informed decisions while choosing appropriate adaptation options. From these findings it would be necessary to develop sound micro-water harvesting technologies, and embrace drought escaping crop varieties among other coping mechanisms to mitigate the negative effects of declining rainfall and the emergent trend of droughts and wet seasons.